WORK-LIFE BALANCE AND SERVANT LEADERSHIP FOR BETTER ORGANIZATIONAL COMMITMENT OF TOURISM EMPLOYEES: THE ROLE OF AFFECTIVE WELL-BEING AS A MEDIATOR - Purwanti Dyah Pramanik; Myrza Rahmanita (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The United Nations compiled the Sustainable Development Goals 2030, which included providing decent work for humankind, such as facilitating employees with a balance among work, family, and private life. This study aims to analyze the relationship among variables and the role of affective commitment between work-life balance and servant leadership partially on employees' organizational commitment in the tourism business. The study applied a quantitative descriptive approach, involving 82 workers in the tourism businesses in Jakarta who were selected by purposive sampling from January-May 2023. Smart-PLS was employed to analyze the data. The study reported that affective well-being mediates the correlation between work-life balance and servant leadership. The study implies the need to mix human resource management practices to create a positive work environment to strengthen organizational commitment.